The Influence of Islamic Leadership, Religiosity, and Work Discipline with Work Ethic on Teacher Performance in Madrasah - Haekal, T. M.; Wahidmurni, Wahidmurni; Zuhriyah, Indah Aminatuz (JURNAL AL-TANZIM, 2023)
This research aims to find out the influence of Islamic leadership, religiosity, and work discipline with work ethic on teacher performance in State Madrasah Aliyah throughout Malang Raya. This research uses a quantitative approach with a correlational type. The population consisted of 224 teachers and 144 samples (simple random sampling) who were given a questionnaire. Data analysis using Smart PLS V.3.2.8. The research results found that Islamic leadership and religiosity positively and significantly affected teacher performance. In contrast, work discipline did not have a significant effect. Work ethic has a positive and significant influence on teacher performance. Although Islamic leadership does not directly influence teacher performance through work ethic, religiosity does not directly influence teacher performance through work ethic. Work discipline, although indirect, has a positive and significant impact on teacher performance through work ethic. In conclusion, certified teachers meet teacher performance standards in madrasas. This research has implications for the management and development of human resources in madrasas, especially in improving teacher performance, which should be carried out in a planned, systematic and sustainable manner through the total involvement of all parties.